Spanish and Latin American women writers in the literry canon: a paratextual study of anthologies of fantastic literature (1946-2016) - García, Patricia (2018)
While it is evident that there are outstanding women authors of the fantastic in Spain and Latin America since the nineteenth century, it is not as clear whether these writers are fairly represented in the corpus available to readers. To what extent are women authors part of the fantastic canon? Are there female reference points for new generations of women writers? To explore processes of canon formation in the literature of the fantastic from a feminist perspective, this article gathers paratexts from 110 anthologies. Employing a quantitative approach with regard to indexed authors, the first section addresses specific questions related to gender and the fantastic in the Hispanic context by analysing statistical data. The empirical study is complemented by an analysis of how the female author is presented and constructed through the discourse in introductions, forewords and other paratextual materials of these anthologies.